Unsteady boundary layer flow of sphere filled with nanofluid in the present of magnetic fields - Ismail, Mohamad Alif; Mohammad, Nurul Farahain; Shafie, Sharidan (Trans Tech Publication, 2019)
The development of boundary layer flow problem which is involve of nanofluid for improve thermal efficiency in many applications is gaining momentum as most of base fluid are not very good thermal conductor. The enhancement of thermal conductivity can be improving when the magnetic fields is presented. Also, by using this material may encountered another problem such as separation flow. This research is study about magnetic fields effect on unsteady mixed convection flow on nanofluid past a sphere with heat flux as its boundary condition. This problem will consider its mathematical model where it can help to predict the solution in experimental method. The mathematical method that being used is Keller-box because of its ability to solve non-linear equation. The nanoparticles that being choose are copper and titanium oxide with water as based fluid. There will have three equation which is mass, momentum, and energy equation. All equations are transform into non-similarity ordinary differential equations by using appropriate variables. The effect of magnetic parameter on velocity and temperature profiles as well as skin friction and Nusselt number are studied. The results show that volume fraction affected the heat-transfer rate, and skin friction coefficient. This study also shows that magnetic parameter affected the separation times which is decelerated the flow.